Waqf and Microfinance Integration Strategy In Improving Welfare Through Community Economic Empowerment - Siti Darajatun; Makhrus (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2025)
Poverty and economic inequality remain persistent challenges in Indonesia, particularly in underdeveloped regions. Although waqf and microfinance have individually contributed to poverty alleviation, limited studies have examined their integrated application for sustainable community empowerment. This study addresses that gap by investigating how the Al-Qur’an Waqf Agency (BWA) and the Micro Waqf Bank (BWM) integrate waqf and microfinance to improve community welfare. The objective is to analyze the strategies, outcomes, and sustainability of their programs in supporting micro and small enterprises. Using a qualitative field research method, data were collected through purposive sampling and in-depth interviews with institutional stakeholders and beneficiaries. Inductive analysis was employed to identify key themes and patterns. The findings indicate that the integration of waqf and microfinance enhances access to capital, improves financial literacy, and strengthens microenterprises, particularly in remote areas. Offline initiatives such as da’wah campaigns are complemented by digital platforms, significantly expanding outreach and public engagement. The study concludes that combining Islamic philanthropy and microfinance offers an effective model for inclusive and sustainable economic development. The implications highlight the need to strengthen digital infrastructure, enhance financial education, and foster multi-stakeholder collaboration. This research contributes to policy formulation and practical strategies for leveraging Islamic social finance to address structural poverty and build resilient local economies.